Emergent emergency response: Speed, event suppression and the chronopolitics of resilience. (April 2019) - Zebrowski, Chris
Emergency responses are premised on the hope that, even when events cannot be wholly predicted and prevented, timely action in the present can be exercised to strip an emergent event of its disruptive potential. Yet, while the speed of emergency responses plays a critical role in underpinning UK resilience, it has been a relatively neglected subject in studies of resilience advanced through the paradigm of preparedness. This article aims to contribute to and extend work in the field of emergency governance by arguing that concerns surrounding the speed of response contribute to a distinct form of security enacted in contemporary emergency response strategies, which I term 'event suppression'. Drawing on policy analysis, preparedness exercise observations and practitioner interviews, this article investigates how speed operates as a core problematic informing the design of UK emergency responses, organized through the Integrated Emergency Management framework. Integrated Emergency Management promises to accelerate emergency response operations by utilizing advances in communications technologies to drive the bottom-up emergent self-organization of emergency responses. Event suppression ensures security not by preventing an event from happening, but by quickly closing down the 'disruptive' time of the emergency event and restoring the linear historical time of standard political processes.